The Role of Zakat Institutions in Supporting the Economy during the Covid-19 Pandemic - Aziz Maulana Akhsan; Muhammad Nafik Ryandono (AFEBI Islamic Finance and Economic Review, 2021)
This study aims to analyze the role of the Zakat Institution in sustaining the economy during the Covid-19 pandemic outbreak. . After the Covid-19 outbreak at the end of 2019 and declared a global pandemic by WHO in January 2020, including in Indonesia. The existence of this pandemic makes people have to do Social Distancing, Physical Distancing as an effort to break the chain of transmission. As a result of this policy, the economic pattern became sluggish and decreased so that many lost their jobs, small traders and income decreased drastically due to the low level of consumption. This requires social financial institutions such as Ziswaf to play an active role in maintaining the economic resilience of the community. This study used a qualitative approach with a literature study model, data were obtained from 6 international journals, 4 national journals, social media, electronic media, books. The results showed that the role of the Ziswaf Institution was very urgent in supporting the economy of the people affected by Covid-19.Keywords: Zakat, Economy, Covid-19